Transformasi Pendidikan Di Lembaga Raudlatul Athfal: Strategi Menghadapi Tantangan Zaman Kekinian - Trismayanti, Euis (Jurnal Riset Multidisiplin Edukasi, 2025)
This qualitative case study research examines the educational transformation strategy in Raudlatul Athfal (RA) in facing the challenges of today's times. Based on the constructivist theories of Piaget and Vygotsky, the study explored the implementation of child-centered learning through interviews and observations in urban and suburban RA. The findings show a significant shift towards constructivist strategies such as project-based learning and self-exploration, which increases children's active engagement and creativity. Although the implementation varies and faces resource constraints and teacher competence, this transformation is considered effective in preparing children with 21st century competencies.